The Acacia controversy resulting from minority rule at the Vienna Nomenclature Section: Much more than arcane arguments and complex technicalities - Moore, Gerry (2011)
The arguments towards resolving the Acacia nomenclatural controversy put forth by Thiele & al. (2011) are reviewed and rebutted. We argue that a truly pragmatic and, moreover, defensible and equitable alternative to accepting the retypification of Acacia Mill. with a conserved type would be to have the 2006 International Code of Botanical Nomenclature, excluding this retypification, serve as the basis for discussions at the Nomenclature Section of the Melbourne International Botanical Congress in 2011. We, and a large component of the international taxonomic community, and beyond, remain convinced that the minority rule voting procedure used at Vienna on Acacia was inappropriate, resulting in animosity that will without any doubt linger until this situation is rectified. Such a minority rule procedure has never in the history of Nomenclature Sections been implemented before. Exclusion of the Acacia retypification can be achieved through a democratic process by objecting to its inclusion when the printed (2006) Code comes up for adoption at the start of the Nomenclature Section. This is perfectly within the established process that has been used in past Section meetings. The integrity of the Code will suffer permanent damage if the retypification of Acacia Mill. with a conserved type is not removed from the ICBN, especially as it ended up there through a minority decision.The arguments towards resolving the Acacia nomenclatural controversy put forth by Thiele & al. (2011) are reviewed and rebutted. We argue that a truly pragmatic and, moreover, defensible and equitable alternative to accepting the retypification of Acacia Mill. with a conserved type would be to have the 2006 International Code of Botanical Nomenclature, excluding this retypification, serve as the basis for discussions at the Nomenclature Section of the Melbourne International Botanical Congress in 2011. We, and a large component of the international taxonomic community, and beyond, remain convinced that the minority rule voting procedure used at Vienna on Acacia was inappropriate, resulting in animosity that will without any doubt linger until this situation is rectified. Such a minority rule procedure has never in the history of Nomenclature Sections been implemented before. Exclusion of the Acacia retypification can be achieved through a democratic process by objecting to its inclusion when the printed (2006) Code comes up for adoption at the start of the Nomenclature Section. This is perfectly within the established process that has been used in past Section meetings. The integrity of the Code will suffer permanent damage if the retypification of Acacia Mill. with a conserved type is not removed from the ICBN, especially as it ended up there through a minority decision.